Long Non-coding RNA MEG3 Promotes Pyroptosis in Testicular Ischemia-Reperfusion Injury by Targeting MiR-29a to Modulate PTEN Expression - Ning, Jin-zhuo; He, Kai-xiang; Cheng, Fan; Li, Wei; Yu, Wei-min; Li, Hao-yong; Rao, Ting; Ruan, Yuan (Frontiers in Cell and Developmental Biology, 2021)
Increasing evidence shows that the abnormal expression of long noncoding RNAs (lncRNAs) is closely related to the progression of ischemia-reperfusion injury (I/R). Previous studies have reported that lncRNA MEG3 regulates pyroptosis in myocardial and cerebral I/R. However, the underlying mechanism of MEG3 in testicular I/R has not been clarified. The aim of this study was to unravel the mechanism of the MEG3-mediated regulation of pyroptosis during testicular I/R.A testicular torsion/detorsion (T/D) model and an oxygen-glucose deprivation/reperfusion (OGD/R)-treated spermatogenic cell model were established. Testicular ischemic injury was assessed by H&E staining. The expression of MEG3 and related proteins and the level of ROS production in testicular tissues were determined by quantitative real-time PCR, western blotting, MDA and SOD assays and immunohistochemistry. The relative expression of MEG3, miR-29a and related proteins in cells was measured by western blotting and quantitative real-time PCR. Cell viability and cytotoxicity were measured by CCK-8 and LDH assays. The secretion and protein levels of inflammasome signaling proteins were determined by ELISA, immunofluorescence and western blotting. The direct interaction among MEG3, miR-29a and PTEN was validated by a dual luciferase reporter assay and Ago2-RIP.In this study, we found that MEG3 was upregulated in animal specimens and GC-1 cells. In gain- and loss-of-function assays, we confirmed that MEG3 can promote pyroptosis in vivo and in vitro. In addition, we found that MEG3 negatively regulated the expression of miR-29a at the posttranscriptional level and promoted the expression of PTEN,and further promote pyroptosis.. Therefore, we investigated the correlation between MEG3 and miR-29a and found that miR-29a was a direct target of MEG3. Furthermore, we found that PTEN was a target of miR-29a. Overexpression of miR-29a effectively eliminated the upregulation of PTEN induced by MEG3, indicating that MEG3 positively regulates the expression of PTEN by sponging miR-29a.In summary, our study indicates that lncRNA MEG3 contributes to pyroptosis by regulating miR-29a and PTEN during testicular I/R, suggesting that this axis may be a potential therapeutic target in ischemic testicular torsion.